Aplikasi Diagnosis Tingkatan Pneumonia dan Saran Pengobatan dengan Fuzzy Tsukamoto - Elyza Gustri Wahyuni; Ahmad Syahriza Ramadhan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Pneumonia is a disease that attacks almost every human being, ranging from young people to adults. Doctors often find it difficult to identify someone who has pneumonia, because pneumonia has several levels of classification, making it possible to experience symptoms that are also different. Pulmonary specialist experts classify pneumonia classification to be